Refining the ice flow chronology and subglacial dynamics across the migrating Labrador Divide of the Laurentide Ice Sheet with age constraints on deglaciation. (3rd September 2019) - Rice, Jessey M.; Ross, Martin; Paulen, Roger C.; Kelley, Samuel E.; Briner, Jason P.; Neudorf, Christina M.; Lian, Olav B.
ABSTRACT: The Laurentide Ice Sheet was characterized by a dynamic polythermal base. However, important data and knowledge gaps have led to contrasting reconstructions in areas such as the Labrador Ice Divide. In this study, detailed fieldwork was conducted at the southeastern edge of a major landform boundary to resolve the relative ice flow chronology and constrain the evolution of the subglacial dynamics, including the migration and collapse of the Labrador Ice Divide. Surficial mapping and analysis of 94 outcrop‐scale ice flow indicators were used to develop a relative ice flow chronology. 10 Be exposure ages were used with optical ages to confine the timing of deglaciation within the study area. Four phases of ice flow were identified. Flow 1 was a northeasterly ice flow preserved under non‐erosive subglacial conditions associated with the development of an ice divide. Flow 2 was a northwest ice flow, which we correlate to the Ungava Bay Ice Stream and led to a westward migration of the ice divide, preserving Flow 2 features and resulting in Flow 3's eastward‐trending indicators. Flow 4 is limited to sparse fine striations within and around the regional uplands. The new optical ages and 10 Be exposure ages add to the regional geochronology dataset, which further constrains the timing of ice margin retreat in the area to around 8.0 ka. Copyright © 2019 The Authors. Journal of Quaternary Science Published by John Wiley & Sons Ltd.